Studi Kebutuhan Nyata Air Bersih per Kapita pada Kota Bandar Lampung - Ria Oktaviani Sinia (UNIVERSITAS LAMPUNG, 2019)
This study aims to investigate the amount of clean water demand per capita in Bandar Lampung City, including the factors that affect the clean water needs, the amount of clean water consumption costs, and compare the results of research with clean water needs in Indonesia and other countries. The research location is in the Bandar Lampung City area which covers 20 sub-districts and 126 villages. Data collection on clean water needs was carried out using a questionnaire distributed to 126 households randomly. Based on the results of the analysis that has been carried out, it can be concluded that: (1) The amount of clean water per capita in Bandar Lampung, which is the sum of all types of clean water needs such as drinking/cooking, bathing, washing, and other needs for washing vehicles is 130.44 ltr/person/day. Factors that influence the need for clean water in the City of Bandar Lampung include: respondent characteristics, number of family members, education status, type of work, number of vehicle ownership, and ease of obtaining water. The cost of clean water needs issued by the people of Bandar Lampung City every month ranges from Rp. 127,267.00 up to Rp. 187,449, 0. (4) The results that obtained in this study are far different from the results of Kindler and Russel's (1984), which stated that the average water use for households is 295 liters / person / day. But the results obtained in this study approached the Planning Criteria Set by the Directorate General of Human Settlements, Public Works Agency in 1996, which stated that the Big City, which is a city with a population of 500,000 - 1,000,000 people, has domestic water needs about 120 ltr/person/day until 150 ltr/person/day.